Philosophical aspect of the lexeme "fortune" in Anthony Radivilovsky’s texts - Spivak, Volodymyr (Sententiae, 2018)
The article contains the historico-philosophical analysis of the lexical and conceptual aspects of the concept of “fortuna” in the texts of Antoniy Radyvylovs’kyj (further A.R.). This problem has not been studied by historians of philosophy yet. The analysis is carried out in the context of Ukrainian moral thought of the Baroque period (1610 - 1680-s). The author proposes the historico-philosophical interpretation of A.R.’s use of the lexeme fortuna and its doublets on the basis of Vilen Gorsky’s methodology. For the first time it has been proven that: (1) the lexeme fortuna was usually translated by Ukrainian intellectuals of the Baroque period as “happiness”; (2) but the fortuna was interpreted by A.R. as the instrument in God’s hands and, therefore, may have either a positive or a negative meaning, depending on the divine providence and the moral virtues of a Christian; (3) the special aspects of how A.R. used the lexical item fortuna and its doublets are: a) the preacher used a Latin lexeme fortuna which is not typical for his entourage; b) depending on the situations, these lexical items may be interchangeable or get specific connotations; (4) in the texts of A.R. the content of the lexeme “fortuna” had not been a full-fledged philosophical concept yet, however it constituted an element of the worldview and beliefs about human destiny, luck, abilities, and happiness; but at the same time A.R.’s views on the fortune are directly based on the texts of ancient and modern Stoics: in particular, Seneca, Boethius, and Lipsius.